Gestalterinnen Frauen, Design und Gesellschaft im Wien der Zwischenkriegszeit - Shapira, Elana; Rossberg, Anne-Katrin (De Gruyter, 2023)
Women designers, many of them Jewish, played a decisive role in the development of Viennese modernity during the interwar period. This book presents new research on designers, photographers, journalists, and patrons who engaged with the prejudices of the time and created new visual languages in order to make careers for themselves. At the same time, they contributed to critical discourse about the emancipation of women.